INTRODUÇÃO AO ENSINO DE FÍSICA NUCLEAR PARA PROFESSORES DO ENSINO MÉDIO, EM MODALIDADE EAD - Schäffer, Décio (2021)
Physics studies natural phenomena is a Science based strongly on experimental processes, in which its hypotheses and theories are confirmed and/or modified by successive verifications, which sometimes modify understanding and add new concepts. Nuclear Physics, in turn, is concerned with unveiling the atomic nucleus, revealing it’s both static and dynamic properties. As static properties are understood those related to the study of electrical load, size and shape, mass, and bonding energy, among others. Dynamic properties refer to the understanding of radioactivity, excited states, nuclear reactions, among others. The advance of Nuclear Physics occurs especially by the different experimental devices, always accompanied by hypotheses, which lead to theories. Thus, what we have in books and scientific articles are theoretical reports of experimental results, which are difficult to reproduce in the classrooms. With this, Nuclear Physics is considered an area that contains its own vocabulary, the well-known ”jargon”, and aggregates concepts from other areas of physics, among which we have Classical and Quantum Mechanics, Relativity, Statistical Mechanics, Electromagnetism and Thermodynamics, and therefore is often taken as an arid terrain to traverse, while a Science that studies the world of order between 10􀀀15 and 10􀀀18 m. Physics has a characteristic of being recognized for usability, utility in scientific and industrial, medical, agricultural areas, in short, it is found in all areas of knowledge to a lesser or greater degree. And unfortunately, there is today a gap in what is learned in high school on physics and what happens in our daily lives, whether in the form of Technology, or in basic knowledge that can give conditions for the formation of more critical and active citizens in society. To make this approach, of what is learned in the School and the reality of the world around us, the new Common National Curriculum Base from Brazil was proposed, and in its text indicates the presence of various concepts that are studied in Nuclear Physics. On the other hand, due to many undergraduate courses in physics, and in the Baccalaureate, nuclear physics, or some discipline that deals with this theme, there is thus a gap in the training of physics teachers. In this sense, this paper proposes an Introduction Course to The Teaching of Nuclear Physics, for high school teachers, contemplating the didactic transposition, proposed by Chevallard. Moreover, aware that currently time is a variable of strong impact on the lives of high school teachers, an introductory course of Nuclear Physics was proposed on the Google Classroom platform, in the well-known Distance Education system, which is a Virtual Learning Environment. The main objective of this choice is the fact that the teacher has the practicality in choosing his/her schedules and days, to make this advance in his/her education.